Experience of Intimate Partner Violence among Women in Sexual Unions: Is Supportive Attitude of Women towards Intimate Partner Violence a Correlate? - Richard Gyan Aboagye (Healthcare, 2021)
Intimate partner violence (IPV) is predominant in sub-Saharan Africa (SSA), with nearly 40 percent of women reporting IPV at some point in time. In this study, we investigated whether a supportive attitude towards IPV is associated with past-year experience of IPV among women in sexual unions in SSA. This study involved a cross-sectional analysis of data from the Demographic and Health Survey (DHS) of 23 countries in SSA. Bivariate and multivariable binary logistic regression analyses were performed to determine the association between attitude towards IPV and past-year experience of IPV. The regression results were presented in a tabular form using crude odds ratio (cOR) and adjusted odds ratio (aOR) at 95% confidence intervals (CIs). In the pooled countries, we found that women who had supportive attitude towards IPV were more likely to experience IPV compared to those who rejected IPV (cOR = 1.72, 95% CI = 1.64, 1.79), and this persisted after controlling for maternal age, marital status, wealth, maternal education level, place of residence, and mass-media exposure (aOR = 1.72, 95% CI = 1.64, 1.79). The same trend and direction of association between attitude towards IPV and experience of IPV was also found in all the 23 studied countries. This study has demonstrated that women who accept IPV are more likely to experience IPV. Hence, we recommend that efforts to end IPV must focus primarily on changing the attitudes of women. This goal can be achieved by augmenting women’s empowerment, education, and employment interventions, as well as sensitizing women in relation to the deleterious ramifications of accepting IPV. Furthermore, reducing IPV is critical towards the achievement of Sustainable Development Goal 3.